Augmented Retail Marketing: Comprehending Customer Satisfaction by AR Marketing Media - Tito Suryawijaya; Diana Aqmala (International Publisher (YAPENBI), 2023)
This research aims to explore the role of Augmented Reality (AR) as a marketing medium in the context of the post-pandemic retail sector. This research adopts a quantitative approach using the SEM - PLS model. Data was obtained through an online survey using a Google Form-based questionnaire filled out by 100 respondents who had used the AR feature to purchase retail products more than twice. Research findings indicate that AR has great potential to increase customer satisfaction and influence consumer purchasing behavior in the post-pandemic retail sector. The implication of this research is that retail companies can utilize AR technology as an effective marketing tool to improve consumer experience, customer satisfaction and business growth. This research also contributes to the AR-based marketing literature, especially in the post-pandemic retail sector, which can be called